On the alleged normative significance of a platitude. (2nd August 2018) - Gaultier, Benoit
Abstract: It seems to be a platitude that the belief that p is correct iff it is true that p . And the claim that truth is the correct‐making feature of belief seems to be just another way of expressing this platitude. It is often thought that this indicates that truth constitutes a normative standard or criterion of correctness for belief because it seems to follow from this platitude that having a false belief is believing wrongly, and having a true belief is believing rightly or correctly . In this paper, I aim to show that when we judge the platitude in question to be indisputably true, we do not endorse that truth is normative for belief but merely the triviality that the belief that p is true iff it is true that p.